Exploring the Laryngectomy Pathway Experience—a Mixed‐Method, Patient Journey Mapping Study of Two US Health Centres - Laurie Wennerholm; Clare L. Burns; Elizabeth C. Ward; Jasmine Foley; JK Rasamny; Craig Berzofsky; Gina Palma (International Journal of Language & Communication Disorders, 2026)
ABSTRACT Background Consensus guidelines advocate multidisciplinary care to optimise recovery following laryngectomy. However, limited evidence exists regarding the nature of the patient recovery journey or their experience accessing rehabilitation services. Aims This study examined the services accessed by, and experiences of, individuals with a laryngectomy (IWL) in the first 12 months post‐surgery. Methods and Procedures Patient journey mapping methodology was used to explore the healthcare journey and patient experience of 12 IWL across the first 12 months of rehabilitation. Demographics and detailed service data were collated from medical records and later reviewed for accuracy with each participant. Individual interviews were used to explore issues that influenced care experiences, and participants also provided experiential ratings relating to the emotional impact of each appointment (positive/negative/neutral) and the reason for the rating. Journeys were explored collectively as a group, then 3 detailed patient journeys are presented highlighting similarities and differences in participant experiences. Outcomes and Results Participants attended a median (Mdn) of 7 medical visits (range = 4–14), 12 allied health visits (range = 4–45), saw 13 different professionals (range = 6–22), and travelled to 6 locations (range = 2–6) for healthcare. Factors adding to the complexity of the health care journeys included preparation for surgery, nature of surgery (primary versus salvage), access to trained specialists throughout phases of care, coordinating between services, travel and funding for consumables. Despite issues, participants largely rated experiences as positive (Mdn = 77; range = 37%–100% positive). Participant perspectives on issues impacting their healthcare journey formed 6 themes: (1) Preparation for laryngectomy surgery, (2) Recovery post‐surgery (3) Access to skilled and coordinated services, (4) Approach of healthcare staff, (5) Communication difficulties impacting healthcare, and (6) Accessing laryngectomy resources and costs. Conclusions and Implications Following laryngectomy, a wide range of multidisciplinary services are accessed to support recovery and rehabilitation. Examining patient experiences through journey mapping has highlighted challenges that can influence the care pathway. Addressing issues that impact service access and patient experience will assist in enhancing laryngectomy care pathways and improve the patient experience. WHAT THIS PAPER ADDS What is already known on the subject Current care pathways advocate specialist, multidisciplinary care for optimal recovery for individuals with a laryngectomy (IWL). Although existing laryngectomy guidelines specify that a range of specialist services are required, and detail what those services should entail, what this actually looks like and means for IWL as they live this path of recovery, remains largely unexplored. What this study adds to the existing knowledge This work expands the body of evidence in laryngectomy care by exploring the healthcare journeys of a cohort of IWL to better understand the extent of medical and allied health services required in the first 12‐months post‐surgery and the patients’ experiences of that care. This work is the first to use journey mapping, a methodology that provides detailed insights gained from both quantitative and qualitative data to elucidate the patients’ care experience. Understanding the patients lived experience, and any challenges faced, is essential information needed to continue to inform future care optimisation. What are the clinical implications of this study? The collective findings from this study highlight the potential challenges IWL can face accessing care in the post‐acute phase. Participants attended a high number of medical and allied health visits, from a variety of professions and services, and faced several challenges including being prepared for their recovery, accessing skilled professionals, communication with healthcare staff, and costs of necessary consumables/equipment. Healthcare providers, including speech‐language pathologists, must recognise and address these issues where possible, to optimise care and reduce patient burden.